Model of a Collaborative Blended Learning Environment in Internet of Things Courses - Arifin, Ifik; Wibaya, Basuki; Syahrial, Zulfiati (International Journal of Psychosocial Rehabilitation, 2020)
Mastering the Industry 4.0 competencies such as Internet of Things (IOT) effectively due to its nature require enhancement and update to the current instructional design (ID) model. Our research has been conducted in 3 cities involving almost 500 active participants to examine which IT-based learning methods were best for this particular competency. We provided face to face and online intervention through collaborative strategies with half of the group. Several instruments were observed such as assessment through rubrics, questioners, self-assessments, peer-reviews, social and collaborative aspects as well as the role of facilitators. This research was meant to develop instructional design model that suits the requirements and demands for IoT competencies.